Polarization loss in the organic ferroelectric trialkylbenzene-1,3,5-tricarboxamide (BTA) - Gorbunov, Andrey V.; Meng, Xiao; Urbanavičiūtė, Indrė; Putzeys, Tristan; Wübbenhorst, Michael; Sijbesma, Rint P.; Kemerink, Martijn (Physical chemistry, chemical physics, 2017)
We investigate the polarization loss in the archetypical molecular organic ferroelectric trialkylbenzene-1,3,5-tricarboxamide (BTA). We prove that the polarization loss is due to thermally activated R-relaxation, which is a collective reversal of the amide dipole moments in ferroelectric domains. By applying a weak electrostatic field both the polarization loss and the R-relaxation are suppressed, leading to an enhancement of the retention time by at least several orders of magnitude. Alternative loss mechanisms are discussed and ruled out. By operating the thin-film devices slightly above the crystalline to liquid crystalline phase transition temperature the retention time of one compound becomes more than 12 hours even in absence of supportive bias, which is among the longest reported so far for organic ferroelectric materials.